2016
DOI: 10.1007/s00251-016-0924-z
|View full text |Cite
|
Sign up to set email alerts
|

LILRA6 copy number variation correlates with susceptibility to atopic dermatitis

Abstract: Leukocyte immunoglobulin-like receptors (LILR) are expressed mostly on myelomonocytic cells where they are mediators of immunological tolerance. Two LILR genes, LILRA3 and LILRA6, exhibit marked copy number variation. We assessed the contribution of these genes to atopic dermatitis (AD) by analysing transmission in 378 AD families. The data indicated that copies of LILRA6 were over-transmitted to affected patients. They are consistent with a contribution of LILR genes to AD. They could affect the equilibrium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…With regard to AD, CNV within FLG is reported to make a significant, dose-dependent contribution to the risk of disease development. CNVs of some other genes have been also reported (Chen et al, 2013;Li et al, 2016;Lopez-Alvarez et al, 2016). Here, we performed allelotyping analysis in AD patients in Japan to discover uncharacterized genetic factors for AD.…”
Section: Introductionmentioning
confidence: 95%
“…With regard to AD, CNV within FLG is reported to make a significant, dose-dependent contribution to the risk of disease development. CNVs of some other genes have been also reported (Chen et al, 2013;Li et al, 2016;Lopez-Alvarez et al, 2016). Here, we performed allelotyping analysis in AD patients in Japan to discover uncharacterized genetic factors for AD.…”
Section: Introductionmentioning
confidence: 95%
“…KIR A/B haplotype-defining genes). To date, 21 published studies (comprising >20,000 samples in total) including investigations of KIR disease association, function, expression and imputation have utilised the method [ 13 , 31 , 34 , 38 , 43 , 45 60 ]. A KIR typing service using qKAT has also been established at the Addenbrooke’s Hospital Histocompatibility and Immunogenetics (Tissue Typing) laboratory in Cambridge (UK).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the interaction with human leukocyte antigen (HLA) class I molecules, human LILRAs are categorized into LILRA group 1 (LILRA1–3) and LILRA group 2 (LILRA4–6) members [ 7 , 10 ]. Moreover, LILRAs have been demonstrated to play important roles in infection or autoimmune diseases such as HIV infection [ 11 ], multiple sclerosis [ 12 ], atopic dermatitis [ 13 ] and rheumatoid arthritis [ 14 ]. It has been reported that LILRA1, 3, 4 and 5 bind with HLA-G, HLA-C and classical HLAs [ 3 , 7 , 11 , 13 , 14 ] and regulate adaptive or innate immune pathways such as the ERK/MEK [ 15 ], TLR [ 3 ] and JNK/p38MAPK [ 16 ] signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LILRAs have been demonstrated to play important roles in infection or autoimmune diseases such as HIV infection [ 11 ], multiple sclerosis [ 12 ], atopic dermatitis [ 13 ] and rheumatoid arthritis [ 14 ]. It has been reported that LILRA1, 3, 4 and 5 bind with HLA-G, HLA-C and classical HLAs [ 3 , 7 , 11 , 13 , 14 ] and regulate adaptive or innate immune pathways such as the ERK/MEK [ 15 ], TLR [ 3 ] and JNK/p38MAPK [ 16 ] signaling pathways. Additionally, they have been reported to upregulate the cytokines IL-1R, IL-4, IL-6, IL-10, IL-12, IL-17, TNFα and IFN-γ [ 3 , 7 , 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation